A Comparative in Vitro Study of Apical Microleakage of Five Obturation Techniques - Manuel Monterde; Antonio Pallarés; Cristina Cabanillas; Ignacio zarzosa; Alejandro Victoria (University of Zagreb. School of Dental Medicine, 2014)
Aim: A comparison was made between the root canal lateral condensation technique and other condensation techniques in which physical (temperature: Soft-Core®, Obtura II®) or chemical changes (condensation: Guttaflow®, Resilon®) may affect the dimensional stability of obturation and thus favor apical microleakage. Materials and methods: A total of 212 single-root teeth removed for orthodontic or periodontal reasons were randomized to 5 groups of 40 teeth each. Six samples were used as positive controls, and another 6 as negative controls. The teeth were worked with the Hero 642 system, and each group was obturated using a different technique: lateral condensation, Obtura II®, Soft-Core®, Guttaflow® or Resilon®. The samples were immersed in black ink, and after 72 hours the teeth were transparentized using the technique described by Robertson. Filtration of the ink was measured under the stereoscopic microscope. Analysis of variance and post-hoc testing were used for the statistical analysis.Results: The Soft-Core® obturated group showed significantly greater microleakage than the other groups, with no differences among the rest of the groups. Conclusions: Under the conditions of this study, the teeth obturated with the Soft-Core® technique showed greater apical microleakage than the other systems.